PHASE BEHAVIOR PREDICTION FOR HYDROCARBONS/CARBON DIOXIDE/WATER SYSTEMS AT LOW TEMPERATURES - YONG, WEN PIN (2015)
Although low temperature carbon dioxide (C02) flooding can achieve high displacement efficiency, it exhibits complex multicomponent and multiphase systems with the presence of both nonpolar (hydrocarbons and C02) and polar (water) compounds. This study evaluates the performance of advanced association models, statistical associating fluid theory (SAFT) EoS and cubic plus association (CPA) EoS and classical cubic models, Soave-Redlich-Kwong (SRK) EoS and Peng Robinson (PR) EoS in representing the phase behavior of binary, ternary and multicomponent hydrocarbon/C02/water mixtures. Phase equilibrium experiments are conducted to observe the multi-phase formation of high and medium molecular weight hydrocarbon/C02/water systems at 40 volume% water content and low temperature (298.15 K) conditions. The experimental results are then correlated with the models.